Inter-regional contacts and voting behaviour in Belgium: What can we learn from the 2019 elections?. Issue 3 (27th May 2021) - Thijssen, Peter; Reuchamps, Min; De Winter, Lieven; Dodeigne, Jérémy; Sinardet, Dave
ABSTRACT: The 2019 elections in Belgium yielded contrasted results between the two main regions of the country, Flanders and Wallonia. It is often posited that at the core of this regional difference is the intermingled question of identity and state reform preferences. In this context, this article asks the following question: does the presence or absence of inter-regional contacts can explain voting behaviour? To answer this question, we use structural equation modelling in order to compare 2019 voting behaviour in Flanders and in Wallonia. We rely on the 2019 RepResent cross-sectional post-electoral survey that offers a representative sample of the population in both regions, including indicators of their inter-regional contacts and vote choice.